2001
DOI: 10.1046/j.1365-3040.2001.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐induced protection against death of suspension‐cultured apple fruit cells exposed to low temperature

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…One of these (ACR556) encodes the defenserelated enzyme caffeic acid 3-O-methytransferase (COMT), one of the principal enzymes in the complex network of reactions occurring as part of lignin biosynthesis and involved in the level of cell wall crosslinking in lignified tissues (Lee et al 1997). Thus, the observed changes in ACR556 transcript level may indicate that heat conditioning could have an effect on cell wall fortification, supporting the idea that a prior heating may retard chilling-induced physical changes in cell structure and function (Wang et al 2001). Other genes (ACR86 and ACR659) within group 2 were homologues to proteins involved in oxidative stress.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…One of these (ACR556) encodes the defenserelated enzyme caffeic acid 3-O-methytransferase (COMT), one of the principal enzymes in the complex network of reactions occurring as part of lignin biosynthesis and involved in the level of cell wall crosslinking in lignified tissues (Lee et al 1997). Thus, the observed changes in ACR556 transcript level may indicate that heat conditioning could have an effect on cell wall fortification, supporting the idea that a prior heating may retard chilling-induced physical changes in cell structure and function (Wang et al 2001). Other genes (ACR86 and ACR659) within group 2 were homologues to proteins involved in oxidative stress.…”
Section: Resultsmentioning
confidence: 85%
“…Chilling injury (CI) results from exposure to low, nonfreezing, temperature and eventually ends up with cell death (Wang et al 2001). Most of the knowledge about the molecular cold responses arises from studies conducted with the chilling-tolerant plant Arabidopsis thaliana (Seki et al 2001;Thomashow 2001), while research on chilling-sensitive plants has been rather scarce.…”
Section: Introductionmentioning
confidence: 99%
“…To establish whether AP2D7 is transcriptionally regulated by cold, apple cell cultures (Wang et al, 2001) were treated with cold (1°C) or cold followed by a 25°C treatment. Expression analysis revealed that AP2D7 was strongly regulated by cold (Fig.…”
Section: Cold Regulation Of Ap2d7/cbf2 In Cell Culturementioning
confidence: 99%
“…Briefly, protoplasts were suspended in PBS containing 50 lg PI ml À1 plus 0.1% Triton X-100 (v/v) and 60 lg ml À1 RNase (w/v) and the protoplasts were analyzed by the use of a flow cytometer (ESP Elite, Coulter). Cells undergoing PCD appeared in the cell cycle distribution as cells with a DNA content of less than that of G 1 cells and were estimated with Listmode software (Wang et al 2001).…”
Section: Dna Extraction and Analysismentioning
confidence: 99%